Overview of Listeria monocytogens and its epidemiology : a potential threat for pregnant women - Neha, Shaba Binte Hafiz (Brac University, 2022)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Microbiology, 2021.